Organic matter availability and management in the context of integrated soil fertility management in sub-Saharan Africa - Vanlauwe, Bernard (Royal Society of Chemistry, 2012)
Appropriate management of organic resources is fully embedded in the Integrated Soil Fertility Management (ISFM) framework. ISFM aims at maximising the use efficiency of external inputs through the use of improved germplasm, well-managed fertiliser and organic inputs, and adaptation of any practices to prevailing local farming conditions, including the management of non-responsive soils, or soils on which crops do not respond to fertiliser application. After a summary of the role of organic resources in tropical soil fertility management as affected by changing paradigms, the organic resource quality concept is introduced and important observations regarding the current availability and use of organic inputs in African smallholder farming systems are highlighted. The role of organic resources within ISFM is explored in the following ways: (i) ISFM as an entry point for producing organic resources in situ, the most viable mode of organic resource acquisition in African smallholder systems; (ii) the occurrence of and mechanisms underlying positive interactions between organic inputs and fertiliser, specifically focusing on the role or organic resource quality; (iii) organic resources as a solution to site-specific constraints, including high phosphorus sorption, soil acidity or soil erosion; and (iv) the potential role of organic resources in rehabilitating non-responsive soils. In a last section, the potential impact of ISFM on soil organic matter stocks and quality are addressed. In summary, although ISFM cannot be implemented without organic resources, the ISFM framework takes into account the realities of organic resource availability at the smallholder farm level.